Multiwalled Carbon Nanotubes/CsPbX3@Polyacrylonitrile Core/Shell Nanofibers with Ultrahigh Water, Thermal, and Ultraviolet Stability - Huang, Yongjun; Wang, Tingting; Zheng, Jianzhong; Li, Feiming; Lan, Wangrong; Zheng, Fengying; Li, Shunxing (Macromolecular materials and engineering, 2021)
The application of all‐inorganic perovskite nanocrystals (PNCs) is considerably limited by their inherent instability under the ubiquitous environmental conditions with high water content, temperature, and UV intensity. The multiwalled carbon nanotubes (CNTs) are combined with polyacrylonitrile (PAN) for the first time to improve the uniform luminous performance and environmental stability of PNCs, attributing to the dense growth of PNC via lead ions bound with rich carbonylation on CNT surfaces, the excellent characteristics of CNTs (including hydrophobicity, electrical conductivity, specific heat, UV absorption capacity), the weather resistance of PAN polymer, and their synergistic effect. Here, via one‐step single‐nozzle electrospinning at room temperature, CNTs, PNCs, and PAN are comprised as core–shell nanofibers (i.e., CNTs/PNCs@PAN) with tunable emissions between 472 and 683 nm, covering the visible light range from blue to red. The photoluminescence intensity of CNTs/CsPbBr3@PAN can be 93%, 91%, and 91% of the initial value, respectively, after being immersed in water for 20 days, heated to 90 °C, and exposed to 365 nm light irradiation for 48 h, which are superior to those of the previously reported PNCs/PAN fibers. The ultrahigh water stability is further proven by CNTs/PNCs@PAN‐based sensor for rhodamine 6G solution fluorescence detection. The core/shell nanocomposite fibers are prepared via a one‐step single‐nozzle electrospinning process, which shows tunable emission between 472 and 683 nm. More interestingly and surprisingly, the in situ growth of perovskite nanocrystals (PNCs) in nanofibers can greatly improve the fluorescence stability due to the synergistic effect of the weatherability of polymers, the regular arrangement of carbon nanotubes (CNTs), the chelation of CNTs with PNCs, and the constraints of nanofibers.